2019
DOI: 10.1111/jcmm.14690
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA PART‐1 targets TGFBR2/Smad3 to regulate cell viability and apoptosis of chondrocytes via acting as miR‐590‐3p sponge in osteoarthritis

Abstract: Osteoarthritis (OA) is a degenerative joint disease that commonly occurs in the elderly. This study focused on apoptosis and explored the modulating effects of long non‐coding (lncRNAs) prostate androgen‐regulated transcript‐1 (PART‐1) on chondrocytes apoptosis. In the present study, the PART‐1 expression level was down‐regulated in the OA cartilages. Silence of PART‐1 decreased the cell viability and promoted chondrocytes apoptosis. Overexpression of PART‐1 could reverse the effects induced by interleukin 1β … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 28 publications
(49 reference statements)
1
16
0
Order By: Relevance
“…Here we identified miR-495 could target TGFBR2, a gene with important role in chondrocyte phenotype [15]. In this research, we found that TGFBR2 expression was lower in OA patients and IL-1β-challenged chondrocytes, which was also like that in previous study [18]. Shen et al suggested that TGFBR2 deletion could promote OA-like injury in mice [16].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Here we identified miR-495 could target TGFBR2, a gene with important role in chondrocyte phenotype [15]. In this research, we found that TGFBR2 expression was lower in OA patients and IL-1β-challenged chondrocytes, which was also like that in previous study [18]. Shen et al suggested that TGFBR2 deletion could promote OA-like injury in mice [16].…”
Section: Discussionsupporting
confidence: 80%
“…Chen et al reported that TGFBR2 was targeted via lncRNA MEG3 to suppress extracellular matrix degradation of chondrocytes [17]. Furthermore, Lu et al TGFBR2 could suppress chondrocytes apoptosis in OA [18]. These previous reports have confirmed that TGFBR2 could attenuate chondrocytes apoptosis and extracellular matrix degradation induced via IL-1β.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In OA patients, the high expression of PART1 upregulates the expression of SOX4 through the ceRNA miR-373-3p , thus promoting the increased expression of MMP-13, ADAMTS4, and ADAMTS5, resulting in ECM degradation. 51 Interestingly, Lu et al 52 studied chondrocytes in OA patients and found that the expression of PART1 in OA decreased. Silencing PART1 in primary chondrocytes induced by interleukin (IL)-1β can reduce cell viability and induce apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…So far, a number of lncRNAs have been reported to possess promising prognostic or diagnostic value for OS (15,16); however, the role of prostate androgen-regulated transcript 1 (PART 1) in this malignancy is largely unknown. Recently, studies by showed that PART1 regulated the apoptosis of chondrocytes in osteoarthritis (17). A recent study by investigated the functions of PART1 in hepatocellular carcinoma and found that PART1 served as oncogenic lncRNA through sponging miR-590-3p to upregulate HMGB2 expression in hepatocellular carcinoma (18).…”
Section: Introductionmentioning
confidence: 99%